The Effect of Green Finance Implementation on the Value of Transportation Companies Listed on the Indonesia Stock Exchange - Fatima, Faudya Nurul; Darman, Darman; Fattah , Vitayanti; Fera, Fera (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the impact of Green Finance implementation on the value of transportation subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. Green Finance is measured using the Green Finance Index (GFI) based on six sustainability indicators, while company value is proxied by the Price to Earnings Ratio (PER), Price to Book Value (PBV), and Tobin's Q. The research sample consisted of 9 companies selected through purposive sampling, with simple regression analysis as the testing method. The results indicate that Green Finance implementation has no significant effect on company value. Descriptive trends also show that high levels of GFI implementation do not always align with increases in PER, PBV, or Tobin's Q, so that sustainability practices are still perceived by the market as a short-term cost burden rather than a driver of added value. This finding confirms that Green Finance's contribution to the value of transportation companies is still limited. The practical implication of this study is the need for regulatory support and strengthening the integration of sustainability practices so that Green Finance can increase company credibility in the eyes of investors and encourage long-term value creation.